The nexus of nurse work-life balance on performance: a case in private hospital - Adella, Adella; Antonio, Ferdi; Massie, Roy G.A. (Intelektual Pustaka Media Utama, 2024)
The healthcare organization is highly competitive, in which excellent service becomes crucial. As part of the healthcare front-liners, nurses become the main provider of such services, especially in private hospitals. Therefore, it is essential to enhance nurse performance to ensure hospital success. This study investigated the relationship between work-life balance (WLB) on nurse performance (NP) mediated by work engagement (WE) and psychological well-being (PWB). This cross-sectional study recruited 132 eligible nurses in a internationally-accredited type B private hospital (>200 beds). The proposed model of this study is analyzed using partial least square-structural equation modeling (PLS-SEM). The association between all studied variables is significant. The relation between WLB on NP mediated by WE and PWB is significant (p-value 0.000, zero fall, CI 95%)-WLB on PWB (ß=0.743), WLB on WE (ß=0.466), PWB on WE (ß=0.379), WE on NP (ß=0.351) and PWB on NP (ß=0.579). This study indicates that nurse WLB should be an essential aspect to consider in enhancing NP. The hospital should also monitor and evaluate WE and PWB in improving NP.